Field-Based Biochar, Pumice, and Mycorrhizae Application on Dryland Agriculture in Reducing Soil Erosion - Surya Sabda Nugraha; Junun Sartohadi; Makruf Nurudin (Applied and Environmental Soil Science)
Biochar, pumice, and mycorrhizae applications using direct testing methods in the field have not been widely carried out. The application of biochar in this study was used as a conservation material to control runoff and erosion. The research was conducted using a field plot during the peak of the rainy season (March-April) of 2021. The study was conducted in areas where the soil material is dominated by clay (>40%) and steep slope angles (>60%). The cropping pattern at the research site is generally cassava in the dry season and corn in the rainy season. Four 1 × 10 m field plots with corn stands were prepared with biochar, pumice, mycorrhizae, and control treatments. Runoff and sediment measurements were carried out by calculating the volume of water and suspension in the storage tank. The effect of three treatments was observed and measured through some soil characteristics such as bulk density (BD), specific gravity (SG), porosity, organic matter content (OM), cation exchange capacity (CEC), and aggregate stability. The highest rainfall in March and April reached 441 mm/month, with the highest intensity reaching 150 mm/week. Under intense rainfall, biochar application provides better performance than pumice and mycorrhizae. Runoff reduction from biochar is the highest, with 51.67%. On the other hand, pumice and mycorrhizae show a lower effectivity in decreasing runoff with 40.15% and 37.92%, respectively. The effectivity on lowering runoff translates to each ameliorant’s performance in reducing soil loss. Biochar decreases soil loss by 50.78%, while pumice and mycorrhizae decrease soil loss by 37.9% and 26.26%. The application of biochar reduced the rate of erosion by altering soil characteristics. Biochar application provides better soil characteristics by reducing BD and SG while at the same time increasing the porosity, OM, CEC, and aggregate stability. The changes provided by biochar can provide means to both soil conservation and increase in soil productivity.